An Intervention to Improve the Writing Skills of Students with Learning Disabilities: Stop & List Strategy - Özbek, Ahmet Bilal; Tülü, Burcu Kiliç; Ergül, Cevriye (Insights on learning disabilities, 2019)
The aim of this study is to examine the effectiveness of the Stop & List strategy instruction on the descriptive text writing performances of students with learning disabilities. e intervention was planned according to the Self-Regulation Strategies Development instructional framework. Three Turkish-speaking fourth-grade students who were diagnosed with learning disabilities participated in the study. Intervention sessions took place once a week for 45 minutes for a total of nine weeks for all participants. e planning and writing scaffoldings that were used in the intervention sessions were prepared by the researchers. Monitoring assessments were held seven and 14 days after the last intervention session of all participants. Students were evaluated in terms of planning time, length and holistic quality of texts and use of transition words. Findings showed that holistic quality and length of texts written by students increased, they used more transition words and used more time for planning. e Stop & List Strategy was found to be effective in improving students' written expression performances. The Findings are discussed further within the framework of the literature.